The Representation of the Feminine in the Portuguese Press : A Content Analysis of the Diário de Notícias Newspaper - Álvares, Cláudia (2012)
This is a brief report of a research project, coordinated by me and funded by the Portuguese Government. It studies ‘The Representation of the Feminine in the Portuguese Press’ (POCI/COM 55780/2004), and works on the content analysis of discourse on the feminine in various Portuguese newspapers, covering the time span of February 1st till April 30th 2006. The paper is divided into two parts: in the first part, I will briefly discuss the typology used to code the text units of selected articles; in the second part, I will explore the most expressive percentages of the first two weeks of February for the content analysis of the Diário de Notícias newspaper. These percentages were obtained with the NVivo 6 qualitative data treatment software programme.